Selfhood and Subjectivity in Sufi Thought: Image of a Mole on Emperor Akbar’s Nose - Dipanwita Donde (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2021)
This paper addresses the making of portrait-images of Mughal emperors, in which distinctness and particularity in individual features distinguished portraits of emperor Akbar from his ancestors and successors. Scholars have argued that the technique of ‘accurate’ portraits or mimesis was introduced to Mughal artists with the arrival of renaissance paintings and prints from Europe, brought by Jesuit priests to the Mughal court. However, the question of why Mughal emperors saw a need to arrive at portraiture in the likeness of individuals remains to be addressed. This paper argues that the desire to portray a ruler, in all his individual particularity, can arise only within a literary and intellectual matrix in which the individual is valued and where ideas about selfhood and subjectivity have already permeated the philosophical, political, and literary thought. Tracing the transhistorical and transcultural migration of ideas and motifs from Timurid Central Asia to Mughal India, this paper examines the transference of Sufi thought on image-making practices, particularly portraiture, in the imperial court of the Mughals in early seventeenth century. Keywords: Portrait-images of Akbar, subjectivity, Sufi thought, poetics between text and image.